2016
DOI: 10.1002/2016ja022521
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for EMIC wave scattering of relativistic electrons in space

Abstract: Electromagnetic ion cyclotron (EMIC) waves have been proposed to cause efficient losses of highly relativistic (>1 MeV) electrons via gyroresonant interactions. Simultaneous observations of EMIC waves and equatorial electron pitch angle distributions, which can be used to directly quantify the EMIC wave scattering effect, are still very limited, however. In the present study, we evaluate the effect of EMIC waves on pitch angle scattering of ultrarelativistic (>1 MeV) electrons during the main phase of a geomag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
84
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 55 publications
7
84
0
1
Order By: Relevance
“…Here we will investigate the 27 February 2014 dropout event in which EMIC wave scattering plays an important role. The effect of EMIC wave scattering at L = 5.77 during this event have been modeled using in situ EMIC wave and plasma data observed by Van Allen Probes based on the quasi‐linear theory (Zhang et al, ). By comparing to the observed loss of radiation belt electrons, they confirmed that EMIC wave‐induced electron scattering was the dominant loss mechanism at L = 5.77.…”
Section: Observations Of Dropout Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we will investigate the 27 February 2014 dropout event in which EMIC wave scattering plays an important role. The effect of EMIC wave scattering at L = 5.77 during this event have been modeled using in situ EMIC wave and plasma data observed by Van Allen Probes based on the quasi‐linear theory (Zhang et al, ). By comparing to the observed loss of radiation belt electrons, they confirmed that EMIC wave‐induced electron scattering was the dominant loss mechanism at L = 5.77.…”
Section: Observations Of Dropout Eventsmentioning
confidence: 99%
“…In contrast, Shprits et al () combined observations and modeling of the evolution of the electron flux pitch angle distribution on 17 January 2013, showing that EMIC waves provide the dominant loss mechanism of radiation belt electrons at ultrarelativistic energies. Zhang et al () also showed direct and quantitative evidence of EMIC wave‐driven relativistic electron losses in the Earth's outer radiation belt by comparing their model results with the local observations of electron pitch angle distributions on 27 February 2014. By examining the data from multiple satellites including Van Allen Probes, THEMIS, and GOES during the 30 September 2012 dropout event, Turner et al (, ) concluded that the losses at L * > ~4 were dominated by magnetopause shadowing and outward transport and the losses at lower L * regions were dominated by wave‐particle interactions.…”
Section: Introductionmentioning
confidence: 97%
“…Li et al ., ]. Previous studies have already provided simultaneous observational evidence that the occurrence of EMIC waves can cause relativistic electron precipitation [e.g., Miyoshi et al ., ; Carson et al ., ; Kersten et al ., ; Usanova et al ., ; Clilverd et al ., ; Zhang et al ., ; Shprits et al ., , ; Su et al ., ]. Plasmaspheric hiss can scatter electrons within a broad range of energies with a longer lifetime (~1–100 days) for >~1 MeV electrons but a shorter lifetime (<~1 day) for <~200 keV electrons [e.g., Abel and Thorne , ; Li et al ., ; Meredith et al ., , ; Summers et al ., ; Thorne et al ., ; L .…”
Section: Introductionmentioning
confidence: 98%
“…Electromagnetic ion cyclotron (EMIC) wave is one of common emissions in the Earth's magnetosphere, whose frequency falls within the range of Pc1–Pc2 (0.1–5 Hz) geomagnetic pulsations (Anderson et al, ; Cornwall, ; Young et al, ). EMIC wave has been considered as an important candidate for heating heavy ions in the inner magnetosphere (Chen et al, ; Gao et al, ; Thorne & Horne, ; Zhang et al, ), scattering ring current protons (Carson et al, ; Xiao et al, ), and the loss of relativistic electrons in the radiation belt (Gao et al, ; Meredith et al, ; Ni et al, ; Zhang et al, ). The thermal anisotropy (T ⊥ > T ∥ ) of hot protons provides the free energy to excite EMIC waves (Anderson et al, ; Chen et al, ; Cornwall, ; Gary et al, ; Lu et al, ; Lu & Wang, ).…”
Section: Introductionmentioning
confidence: 99%